METODE PEMAHAMAN AL-QUR’AN (STUDI KAJIAN TAFSIR AL-QUR’AN DENGAN PENDAPAT SAHABAT) - Ranowan Putra; Amrin Amrin; Adi Priyono (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2022)
The discourse of interpretation does not only rely on two main sources, namely the Qur'an and Hadith, but also on the opinions of the Companions. So that the opinion of the friends becomes one of the references in explaining the general and problematic al-Qur'an that requires law. Tafsir al-Qur'an according to the opinion of the Companions is classified as a product that occurred in classical times because of the interpretation carried out as a reference product. The Companions interpreted the Qur'an with their opinions based on the knowledge and knowledge of the Qur'an in the form of explanations of the meaning and asbabul nuzul which consisted of social contextual society, history of society, causes of heredity, general meaning, and all meanings. contained in the Qur'an which includes fiqh, worship, aqidah, morals related to human life based on its rules: first, the friends in conveying their words must be correlated with the Qur'an and hadith. Second, the Companions who interpret the verses of the Qur'an must pay attention to the instructions that have been outlined. Third, the Companions used ijtihad in explaining the Qur'an without changing the meaning and content of the Qur'an. Thus, the ability to maintain the authenticity and sanctity of the Qur'an as God's revelation and become a major need in the current context in producing solutions to problems that arise requires legal studies.